Proactive personality and Innovative Work Behavior A META-ANALYSIS - Nor Lailla; Nuraeni Nuraeni (Greenation International Journal of Tourism and Management, 2023)
Objective from study This is explore between Innovative Work Behavior and Proactive personality through meta analysis for provide alternative offers more knowledge_ Good about literature Innovative Work Behavior in development organization. Based on exposure results findings search the articles above related meta analysis study Proactive personality and Innovative Work Behavior can concluded a number of study confirm connection positive between Proactive personality and Innovative Work Behavior. With thus, research This conducted in 7 journals with 25 studies for test magnitude connection between Proactive personality and Innovative Work Behavior, and For see influence to connection between Proactive personality and Innovative Work Behavior. From the results discussion connection between Innovative Work Behavior and Proactive personality with meta analysis concluded that the average effect proactive personality increase Innovative Work Behavior of 0.43 or 43% which is included category low. While 57% is influenced by variables other.